Production of antiviral vaccine antigens using a silkworm-baculovirus expression system - Takahiro Kusakabe (Elsevier, 2023)
The outbreak of the SARS-2-CoV infection has become a global outbreak and continues to cause many deaths. In addition, the risk of pandemics continues to increase due to environmental changes and the globalization of human exchange and logistics. On the other hand, our preparedness for emerging infectious diseases caused by such unknown viruses is inadequate, and dealing with viral infections is one of the most important issues that need to be addressed immediately. Vaccine based disease control is considered an ideal countermeasure for infectious diseases, as it is expected to provide maximum efficacy at minimum cost. Although new nucleic acid-based vaccines are leading the way in the prevention of COVID-19, the mainstream of vaccines is still inactivated or live attenuated vaccines that use the pathogen virus itself. Subunit vaccines, in which specific virus-derived proteins are produced as recombinant proteins and used as vaccine antigens, have been developed, but production and development of many antigens that are difficult to mass-produce as recombinant proteins, such as the spike protein antigen of COVID-19 has not progressed.This paper describes the development of recombinant protein vaccines using the silkworm, which has an advantage in the production of such difficult-to-express vaccine antigens, especially virus-like particles.